2002
DOI: 10.1159/000063359
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Topical Hypopigmenting Agents on Solar Lentigines of Asian Women

Abstract: Background: So-called darkened age spots encompass distinct pathological processes. The efficacy of topical depigmenting agents is difficult to objectivate. Objective: To assess the hypopigmenting effect of three cosmetic formulations using objective biometrological methods. Methods: 50 women of South-East Asian ancestry were enrolled in this pilot study. They had solar lentigines according to dermoscopic criteria. The lesions were treated by topical hypopigmenting formulations. Products were applied twice dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 23 publications
1
61
1
2
Order By: Relevance
“…The objective assessment of the extent and severity of skin pigmentation disorders benefited from a series of non-invasive methods [21,22]. In this study, we used instrumental non-invasive methods to assess the melasma changes after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The objective assessment of the extent and severity of skin pigmentation disorders benefited from a series of non-invasive methods [21,22]. In this study, we used instrumental non-invasive methods to assess the melasma changes after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Çok ajanlı karşılaştırmalı bir çalışmada soyanın solar lentigolar üzerinde etkili olduğu gösterilmiştir (43) .…”
Section: Melanozoma Transferi Azaltan Ajanlarunclassified
“…86 In a multiagent comparative trial, soy extract was shown to have a modest effect in lightening solar lentigines. 87 …”
Section: Soymentioning
confidence: 99%